Superstructure Planning of 21 Floor Swasana Building Anami Tower B Klapa Village Project - Yosefus Sirie, Ambrosius (Jakarta Global University, 2022)
The structural planning of building construction is needed to get the mosteffective and efficient dimensions and configuration of the structure. Planninga building structure located in an earthquake-prone area must be plannedaccording to standards, is strong, and is earthquake-safe. The Planning of theSuperstructure of the Swasana Building 21 Floors Anami Tower B the KlapaVillage Project refers to the Procedures for Planning for Concrete Structuresand Buildings of SNI 2847-2019, and the Standards for Planning EarthquakeResistance for Building Structures of SNI 1726-2019. Planning of theSuperstructure of the 21-Story Swasana Building Tower B of the KlapaVillage project uses Etabs V.17 software which includes the planning ofbeams, columns, and floor slabs. Loads that are reviewed for the design ofstructural elements are dead load, live load, and earthquake load.